Primary Health Care Access and Ambulatory Sensitive Hospitalizations in New Zealand. Issue 2 (April 2015) - Milne, Barry John; Parker, Karl; McLay, Jessica; von Randow, Martin; Lay-Yee, Roy; Hider, Phil; Cumming, Jacqueline; Davis, Peter
Abstract : Ambulatory sensitive hospitalizations (ASH) are those thought to be preventable by timely and effective primary health care. Better access to primary health care has been associated with lower ASH rates. Funding increases to primary health care in New Zealand beginning in 2001 led to an improvement in access. Analysis of hospitalizations to all New Zealand public hospitals revealed that, for most age groups, ASH rates did not show long-term reductions from 2001 to 2009, while socioeconomic differences in ASH rates widened across this period. We conclude that increasing funding and access to primary health care will not, by itself, reduce ASH rates. Abstract : Supplemental Digital Content is Available in the Text.